Contested space: The contradictory political dynamics of food banking in the UK. (November 2016) - Williams, Andrew; Cloke, Paul; May, Jon; Goodwin, Mark
This paper offers a critical reappraisal of the politics of food banking in the UK. Existing work has raised concerns about the institutionalisation of food banks, with charitable assistance apparently – even if inadvertently – undermining collectivist welfare and deflecting attention from fundamental injustices in the food system. This paper presents original ethnographic work that examines the neglected politics articulated within food banks themselves. Conceptualising food banks as potential spaces of encounter where predominantly middle-class volunteers come into contact with 'poor others' (Lawson and Elwood, 2013), we illustrate the ways food banks may both reinforce but also rework and generate new, ethical and political attitudes, beliefs and identities. We also draw attention to the limits of these progressive possibilities and examine the ways in which some food banks continue to operate within a set of highly restrictive, and stigmatising, welfare technologies. By highlighting the contradictory dynamics at work in food bank organisations, and among food bank volunteers and clients, we suggest the political role of food banks warrants neither uncritical celebration nor outright dismissal. Rather, food banks represent a highly ambiguous political space still in the making and open to contestation.